Distributions of Groundwater Age under Climate Change of Thailands Lower Chao Phraya Basin - Pinit Tanachaichoksirikun; Uma Seeboonruang (My University, 2020)
Groundwater is important for daily life, because it is the largest freshwater source for domestic use and industrial consumption. Sustainable groundwater depends on many parameters: climate change is one factor, which leads to floods and droughts. Distribution of groundwater age indicates groundwater velocity, recharge rate and risk assessment. We developed transient 3D mathematical models, i.e., MODFLOW and MODPATH, to measure the distributions of groundwater age, impacted by climate change (IPSL-CM5A-MR), based on representative concentration pathways, defined in terms of atmospheric CO2 concentration, e.g., 2.6 to 8.5, for the periods 2020 to 2099. The distributions of groundwater age varied from 100 to 100,000 years, with the mean groundwater age ~11,000 years, generated by climate led change in recharge to and pumping from the groundwater. Interestingly, under increasing recharge scenarios, the mean age, in the groundwater age distribution, decreased slightly in the shallow aquifers, but increased in deep aquifers, indicating that the new water was in shallow aquifers. On the other hand, under decreasing recharge scenarios, groundwater age increased significantly, both shallow and deep aquifers, because the decrease in recharge caused longer residence times and lower velocity flows. However, the overall mean groundwater age gradually increased, because the groundwater mixed in both shallow and deep aquifers. Decreased recharge, in simulation, led to increased groundwater age; thus groundwater may become a nonrenewable groundwater. Nonrenewable groundwater should be carefully managed, because, if old groundwater is pumped, it cannot be restored, with a detriment to human life.
Keywords: MODFLOW; Depression-focused recharge; Groundwater model; Groundwater discharge; Groundwater and Isotope Geochemistry